Role of circulating oxidized LDL: a useful diagnostic risk marker in cardiovascular disease - Mandsorwale, Deepti; Sharma, Bindu; Singh, Munindra Pratap (ScienceRise: Medical Science, 2021)
The aim: to assess levels of circulating plasma ox-LDL in various subgroups with different CVD and their relationship with oxidative stress markers, MDA, catalase, and traditional coronary disease risk factors. Material and methods: a total of 215 subjects divided into four groups comprising 54 healthy controls, patients with the SAP were 52 persons, with the UAP 53 ones, and with the AMI there were 56 persons, respectively. Lipid profile parameters (TC, TG, HDL-C, LDL-C, and VLDL-C), plasma MDA, catalase were estimated by kit methods, TBARS method, and colorimetric assay respectively. Plasma Ox-LDL was estimation by competitive ELISA kit method (Mercodia) with the help of specific monoclonal antibody mAb4Eb. Results were present as mean ± SD, significance level at p-values<0.05 with Student’s unpaired t-test. Data analysis was performed by software package SPSS version 17.0. Results: it showed a highly significant (p<0.001) correlation in SAP, UAP, and AMI except for age in the SAP subgroup, moderately significant (p<0.01). Lipid profile except HDL-C was found highly elevated (p<0.001) in subgroups than in healthy controls. HDL-C was higher (p<0.001) in controls with respect to patient subgroups. Comparison of oxidative stress markers (MDA and catalase) and ox-LDH in control with patient’s subgroup indicates highly significant (p<0.001) correlation. The correlation between SAP & UAP was insignificant (p<0.05), SAP with AMI was significant (p<0.05), and UAP & AMI were highly significant (p<0.001). Large interquartile range in SAP subgroup suggesting scattered deviation in the mean value as compared to UAP and AMI showed in the box and whiskers plot and concluded that significantly elevated level of ox-LDL in SAP, UAP, and AMI subgroups indicate its diagnostic importance of CVD. Conclusions: study concluded that significantly elevated level of ox-LDL in SAP, UAP, and AMI subgroups indicate its diagnostic importance of CVD.